Food and nutrition recognition benchmark: using CAFE computer program to recognize nutrient values (International Journal of Food and Nutritional Sciences, 2023)
In nutritional epidemiology, food frequency questionnaires (FFQs) are commonly utilised; however, the creation of the auxiliary programmes and nutritional databases is not well documented in any of the articles. The structure and content of the The discussion also includes the development of cut-points for data removal and extreme nutrient levels. The CAFE computer application modifies dietary intake based on the amount of fat that is visible on meat as well as the specific fats that are utilised in food preparation. It combines many cereals for breakfast and differentiates text for brands and varieties. Due to the high reported frequency of specific items, several extreme values for carbohydrate, energy, fat, alcohol, and protein were still present when outliers in nutrient intake were excluded. A unique technique for matching text and adaptable, updatable databases are some of CAFE's capabilities. More research should be done to determine how extreme nutrient values affect the FFQ's accuracy in assessing diet in nutritional epidemiology.